Experimental study on condensation and acoustic characteristics of steam underwater injection - Li, Yong; Li, Hui; Zhang, Yonghao; Li, Dongyang; Tan, Sichao (Frontiers in Energy Research, 2023)
Bubbling deaeration is widely applied in marine steam power system, and direct contact condensation (DCC) of steam injected into water under low sub-cooled water is the thermodynamic foundation of this technology. The deaeration process involves complex thermal and hydraulic behaviors, such as violent turbulence, interfacial mass transfer, and multiphase flow etc., which induce significant pressure fluctuation and radiated noise. In this paper, the two-phase flow regimes and acoustic characteristics of DCC of steam injected into water were studied for sub-cooled temperature ranging from 3℃ to 17℃. Using high-speed camera to capture the dynamic plume shape, four typical plumes are found: external chug with encapsulating bubble, oscillating bubble jet, conical and cylindrical jet and cap jet; The underwater acoustic signal is measured synchronously, and the acoustic spectrum is obtained by Fast Fourier transform (FFT). Combined with the plume image, the component sources of the acoustic signal are analyzed. It is found that the first dominant frequency and the second dominant frequency of the acoustic are caused by the evolution of the jet main steam zone and the downstream large steam column respectively; By analyzing the influence of injection parameters on acoustic signal, it is found that steam flow and sub-cooled temperatures have a great influence on acoustic root mean square value and spectrum characteristics. With the decrease of sub-cooled temperature, the main frequency of injection noise signal gradually moves to low frequency. Low frequency noise dominates the radiated noise when the flow field approaches the saturation temperature.